Sustainable pavement recycling: Utilization of cement and asphalt waste dust to improve CBR and permeability - Salisa Chaiyaput; Natthapong Thatmas; Trong Nghia-Nguyen; Vo Nguyen Phu Huan; Lindung Zalbuin Mase; Jiratchaya Ayawanna (Results in Engineering, 2025)
• Asphalt waste dust is a by-product of asphalt production. • Evaluate the feasibility of incorporating asphalt waste dust into recycled pavement materials. • Enhancing suitability as sustainable base-course construction materials. • Asphalt waste dust significantly increased the CBR of pavement recycling. This study aims to utilize asphalt waste dust, a pollutant by-product of the asphalt production process, to improve the quality of recycled pavement materials for use as base course materials, under the standards of the Department of Rural Roads and the Department of Highways, Thailand. The mixture consisted of 70% by weight (wt%) reclaimed asphalt pavement (RAP), 30 wt% crushed rock (CR), 3.5 wt% cement (C), and 20 wt% asphalt waste dust (AD), in comparison to the general pavement recycling (RAP-CR-C). Compaction test, permeability test, California Bearing Ratio (CBR) test, and scanning electron microscope (SEM) analysis were performed under all testing conditions. The highest performance was achieved for the recycled pavement materials, containing 3.5 wt% cement and 20 wt% asphalt waste dust (RAP-CR-C-AD20). The coefficient of permeability was 2.32 × 10 -7 cm/s under pressurized constant head, 2.40 × 10 -7 cm/s under an 8 mm falling head, and 2.59 × 10 -7 cm/s under a 14 mm falling head. The CBR values were 493% at 0.1 in (2.54 mm) penetration and 491% at 0.2 in (5.08 mm) penetration. The RAP-CR-C-AD20 exhibited a low coefficient of permeability but a high CBR, compared to those of RAP-CR-C, and above the minimum base course requirement (CBR > 80%). This study highlights the potential of using asphalt waste dust in pavement recycling as an innovative solution that not only reduces waste but also contributes to sustainable road construction practices.
Keywords: Asphalt Pavement Performance Evaluation; Concrete and Cement Materials Research; Innovative concrete reinforcement materials